A comprehensive review of oral hypoglycaemic drugs and their oral health correlates - Bhardwaj, Nishtha; Mehta, Shivani (International Journal of Research in Medical Sciences, 2025)
Oral hypoglycaemic drugs (OHDs) are vital in the effective management of type 2 diabetes mellitus (T2DM), a widespread metabolic disorder that affects millions globally. While these medications excel at controlling blood glucose levels, they can also lead to significant oral health challenges. This article delves into the various pharmacological classes of OHDs and highlights their potential impacts on oral health, including issues such as dry mouth (xerostomia), periodontal disease, taste changes, delayed healing, and a higher susceptibility to oral infections. It is imperative for healthcare providers, especially dental professionals, to understand these connections, as recognizing the oral health implications of diabetes is essential for delivering comprehensive and effective care to diabetic patients. Proper awareness and proactive management can make a substantial difference in the overall well-being of those living with diabetes.